Epistemology of Teacher Personality Competencies Novel Guru Aini by Andrea Hirata - Farihati, Lulu; Wachid Bambang Suharto, Abdul (International Proceedings of Nusantara Raya, 2024)
In the world of education, teachers play a leading role in realizing educational goals and ideals. Teachers must have competence, including teacher personality competence. On the other hand, the current teacher problem is very complex. Teachers should improve themselves to be able to improve the personality competence of a teacher. Teachers as role models for their students must have a complete attitude and personality that can be used as an idol role model in all aspects of their lives. Personality competency is related to the appearance of the teacher as an individual who is disciplined, has a good appearance, is responsible, has commitment and is a role model. Exploring teacher personality competencies can be done using various media, one of which is through literary works in the form of novels. The novel Guru Aini by Andrea Hirata is one of the literary works (that literary works are portraits of life: data) which raises the theme of the life of a teacher. The aim of this research is to find out in depth the personality competence of the teacher in the novel Guru Aini by Andrea Hirata using a theoretical approach. philosophy of science, namely from an epistemological perspective. This research is library research, namely the data needed to complete the research is obtained from the library in the form of books, encyclopedias, dictionaries, journals, documents, magazines and so on. The results of this research show that in the novel Guru Aini there is an identification of teacher personality competencies, namely: (a) teacher personality competencies which include noble, steady, stable and mature morals, being a role model, religious, authoritative, as well as a sense of pride in being a teacher and trusting self.